Experimental Study of the Influences of Temperature and Thermal Insulation on Stress Corrosion Cracking using 3-point bend test - Cheah , Yuen Hung (IRC, 2021)
Stainless steel type 304 is a susceptible towards stress corrosion cracking (SCC) when it is subjected to tensile stress under a corrosive environment.